A randomized trial of a one-time pest intervention: impact on childhood asthma outcomes. (4th May 2021) - Olson, Carolyn; Leu, Cheng-Shiun; Alper, Howard; Millican, Michael; Reznik, Marina
Abstract: Objectives: To evaluate the effects of a one-time, apartment-level Integrated Pest Management (IPM) intervention on healthcare utilization and asthma symptoms among children with persistent asthma living in households with a pest infestation. Study design: In a randomized controlled trial of 384 children aged 5–12 years with persistent asthma, we assigned 183 to receive IPM and 197 to usual care (UC). The primary outcome was healthcare utilization from hospital and Medicaid claims records. Secondary outcomes included caregiver-reported asthma symptoms, pest infestation levels, missed days of school due to asthma, and rescue medication use. Results: The entire cohort improved over the study period, with significant but equivalent declines in mean healthcare utilization in both groups. IPM group had fewer days with reduced activity due to asthma ( p  = 0.04) and larger declines that fell short of statistical significance in asthma symptom days ( p  = 0.22), severe symptoms ( p  = 0.16), missed school ( p  = 0.27) and rescue medication use ( p  = 0.27). Both roach ( p  = 0.001) and mice ( p  = 0.11) infestations decreased much more in the IPM group than the UC group. Conclusions: After a one-time, apartment-level IPM intervention, we found no difference in health care utilization, but fewer days of reduced activity and consistent suggestive evidence of clinically meaningful improvements relative to usual care across other secondary outcomes. Coupled with the established effectiveness of IPM in reducing allergens and scientific consensus on pest-related allergens as asthma triggers, these findings support adding home pest control to traditional medical management of children with severe asthma.